2020
DOI: 10.3390/biom10030429
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Directly Stimulates Spermatogonial Differentiation, Meiosis, and Spermiogenesis in Zebrafish (Danio rerio) Testicular Explants

Abstract: Cortisol is the major endocrine factor mediating the inhibitory effects of stress on vertebrate reproduction. It is well known that cortisol affects reproduction by interacting with the hypothalamic–pituitary–gonads axis, leading to downstream inhibitory and stimulatory effects on gonads. However, the mechanisms are not fully understood. In this study, we provide novel data demonstrating the stimulatory effects of cortisol on spermatogenesis using an ex vivo organ culture system. The results revealed that cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 93 publications
(168 reference statements)
0
15
0
Order By: Relevance
“…In social cichlids, elevated cortisol levels can be associated with subordinate rank [ 216 ] or with periods of social change [ 14 , 217 , 218 ]. Although recent findings in zebrafish suggest that cortisol can also act as a promoter of spermatogenesis [ 219 ], elevated cortisol levels in fish are generally agreed to inhibit reproduction (for review see Rousseau et al . [ 220 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In social cichlids, elevated cortisol levels can be associated with subordinate rank [ 216 ] or with periods of social change [ 14 , 217 , 218 ]. Although recent findings in zebrafish suggest that cortisol can also act as a promoter of spermatogenesis [ 219 ], elevated cortisol levels in fish are generally agreed to inhibit reproduction (for review see Rousseau et al . [ 220 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Reproduction is under multifactorial control of neurohormones, pituitary hormones, glucocorticoids, growth factors, thyroid hormones as well as a number of gonadal hormones including steroids and peptides (Schulz et al, 2010; Tovo-Neto et al, 2018; Fallah 2019, 2020, 2021; Ma et al, 2020a, b; Tovo-Neto et al, 2020; Li et al, 2020). A number of neurohormones including Gnih (Tsutsui et al, 2000) were shown to be involved in the control of pituitary gonadotropin production (Amano et al, 2006; Moussavi et al, 2012, 2013, 2014; Choi et al, 2016; Paullada-Salmerón et al, 2016; Muñoz-Cueto et al, 2017; Branco et., 2018; Ma et al, 2020 a, b) as well as being involved in paracrine control of gonadal function in fish (Fallah et al, 2019, 2020, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The relative number of spermatozoa per area was estimated as described by Fallah et al, (2019, 2020) and Tovo-Neto et al, (2020) using 20 different histological images (100x objective) per testicular explant. The images were analyzed in ImageJ software (National Institutes of Health, Bethesda, Maryland, http://rsbweb.nih.gov/ij), where background subtraction, threshold adjustment, and watershed separation of particles that resulted in a black and white picture of the highlighted spermatozoa were used to count the relative number of spermatozoa in the control and treatment groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative number of spermatozoa per area was quantified for each treatment. Twenty different fields were captured from a 100x objective lens and analyzed by IMAGEJ Software (available at http://imagej.nih.gov/ij/index.html) for quantification of spermatozoa number according to Fallah et al, (2019Fallah et al, ( , 2020, Tovo-Neto et al, (2020) and Rodrigues et al, (2021). This software allows quantification of several types of cells by limiting the size of the particle.…”
Section: Histomorphometrical Evaluation Of Zebrafish Spermatogenesismentioning
confidence: 99%